Urban income inequality and social welfare - Paul Koster (Tinbergen Institute, 2023)
When income inequality increases when average income levels increase, rises in average income levels might result in inequality costs. This paper develops marginal social welfare measures that account for the possibility that income inequality changes when average income levels change. Applications are given for the city of Amsterdam, The Netherlands. For this city, the income elasticity of the Gini is estimated in the range 0.25-0.48. Estimates of marginal welfare changes vary greatly with model choice. For plausible cases, estimates can be negative, raising doubts whether average income increases are beneficial in rich urban areas with high valuations of equality where income inequality increases in income.
Keywords: A13; D61; D63; E24; 330; Social welfare; income inequality; inequity aversion; post-growth